Sustainable Human Resources Management, a Strategy Toward Sustainable Organizational Development; Emphasizing Social Sustainability with a Fuzzy Dematel Approach - Amir Hossein Adeli Jazeb; Mohammad Mahdi Alishiri; Ali Yaghoubali pourkoundelaji (Journal of Systems Thinking in Practice)
Human assets have become the foremost source of competitive advantage in today's world trade environment. The rise and improvement of the unused concept of maintainable human asset administration is one of the concepts that puts the organization in line with maintainable advancement. For this reason, analysts, senior directors, and administration specialists, by emphasizing and tending to the issue of human resource administration, look to attain the sustainable development of organizations. This research advances the field of Sustainable Human Resource Management (SHRM) by addressing a notable theoretical gap: the integration of social sustainability factors using the Fuzzy DEMATEL approach. Despite the extensive literature on SHRM, there is a scarcity of frameworks that systematically incorporate social sustainability. Our study employs a Systematic Literature Review (SLR) methodology, meticulously outlining inclusion and exclusion criteria for article selection, spanning from 1984 to 2020. We adopted a mixed-method approach combining qualitative assessments with quantitative Fuzzy DEMATEL analysis. Data were gathered through a survey distributed among 17 experts in both corporate and academic settings, ensuring a robust evaluation of social sustainability factors within HRM practices. The research identified critical social sustainability indicators and examined their interrelationships, providing a nuanced understanding of their dynamics within organizations. The findings not only bridge the existing theoretical void but also offer practical frameworks for organizations aiming to enhance their sustainability through HRM. Recommendations for both practice and future research are discussed, emphasizing the need for more empirical studies to validate the proposed framework.